Nyamuk: Peran Pola Gigit dan Pilihan Inang Dalam Kompetensi sebagai Vektor - Forman Erwin Siagian; Janno BB Bernardus; Robiatul Adawiyah; Esy Maryanti (Jurnal Ilmu Kedokteran, 2011)
Mosquitoes act as vector of fatal diseases such as malaria and dengue hemorrhagic fever since a long time ago. Thruits biting, it can transfer diseases from one sick individu to another ‘immunologically naïve’ people. Biting patternsand host preference play an important role in transmission of disease. Those two might differ among species, evenbetween strain from different region. Geographic and some other enviromental play an important role on mosquitoes’sindividual ability. By knowing those factors will built better understanding on the role of mosquitoes on diseasetransmission